Mindfulness facets, trait emotional intelligence, emotional distress, and multiple health behaviors: A serial two‐mediator model. Issue 3 (8th April 2016) - Jacobs, Ingo; Wollny, Anna; Sim, Chu‐Won; Horsch, Antje
Abstract : In the present study, we tested a serial mindfulness facets‐trait emotional intelligence ( TEI )‐emotional distress‐multiple health behaviors mediation model in a sample of N = 427 German‐speaking occupational therapists. The mindfulness facets‐TEI‐emotional distress section of the mediation model revealed partial mediation for the mindfulness facets Act with awareness ( Act/Aware ) and Accept without judgment ( Accept ); inconsistent mediation was found for the Describe facet. The serial two‐mediator model included three mediational pathways that may link each of the four mindfulness facets with multiple health behaviors. Eight out of 12 indirect effects reached significance and fully mediated the links between Act/Aware and Describe to multiple health behaviors; partial mediation was found for Accept. The mindfulness facet Observe was most relevant for multiple health behaviors, but its relation was not amenable to mediation. Implications of the findings will be discussed.